The duchess [large type] : a novel - Steel, Danielle (Random House Large Print, 2017)
Angélique Latham has grown up at magnificent Belgrave Castle under the loving tutelage of her father, the Duke of Westerfield, after the death of her aristocratic French mother. But when he dies, her half-brothers brutally turn her out, denying her very existence. Angélique has a keen mind, remarkable beauty, and an envelope of money her father pressed upon her. To survive, she will need all her resources--and one bold stroke of fortune. Unable to secure employment without references or connections, Angélique desperately makes her way to Paris, where she rescues a young woman fleeing an abusive madam--and suddenly sees a possibility: Open an elegant house of pleasure that will protect its women and serve only the best clients. With her upper-class breeding, her impeccable style, and her father's bequest, Angélique creates Le Boudoir, soon a sensational establishment where powerful men, secret desires, and beautiful, sophisticated women come together. But living on the edge of scandal, can she ever make a life of her own--or regain her rightful place in the world?